Clinical and histopathological characteristics in patients with scarring folliculitis type of acne inversa. Issue 1 (1st January 2017) - Lu, Lingyi; Lai, Huiying; Pan, Zhanyan; Hu, Tingting; Hou, Xiaoxiao; Cao, Ke; Ju, Qiang
ABSTRACT: Objective : This study was designed to study the clinical and histopathological characteristics of patients with the scarring folliculitis type acne inversa in Chinese population. Methods : A total of 21 patients with acne inversa and 6 controls without known dermatological disease were recruited from outpatient department of dermatology and orthopedic surgery. Two-millimeter punch biopsies were taken from 8 patients with acne inversa and 6 controls, fixed in formalin, embedded in paraffin and stained with haematoxylin and eosin prior to histopathological analysis. Results : There were 12 patients (57.14%) belonging to the scarring folliculitis type presented with double comedones, papules, nodules, depressed scars, and were mainly Hurley stage I (66.67%). Many of the scarring folliculitis type were smokers (58.33%), some had a history of occupational exposure (41.67%) and some were overweight (50%), the mean BMI of which is 25.18±3.16 kg/m 2 . Histopathological changes such as perifollicular inflammation can be observed in scarring folliculitis type of acne inversa and controls as well. However, epidermal hyperplasia, follicular hyperplasia, sebaceous gland disappearance, destruction of hair follicle and sebaceous gland, collagen hyperplasia, perivascular inflammation, granulomatous inflammation, Micro thrombus were only seen in scarring folliculitis type. The mean surface area in patients (8073.36±15798.43 μm 2 ) was smaller than that in controls (302059.08±502813.78 μm 2 ), with statistically significant difference. (P = 0.024). Conclusion : The scarring folliculitis type in acne inversa in Chinese population could be characterized by depressed scars, double-ended comedones, epidermal cysts and had high proportion of smokers, or occupational exposure with lower Hurley stage, as well as diminished sebaceous gland. Further studies are needed to clarify the relations between the clinical subtypes of acne inversa and their corresponding genetypes.